Effect of N-Acetyl Cysteine administration to the degree of parasitemia and plasma interleukin-12 level of mice infected with plasmodium berghei and treated with artemisinin (Faculty of Medicine Universitas Indonesia, 2009)
Introduction Protection against malaria requires a cell-mediated immune response which is initiated by releasing interleukin-12 (IL-12) from antigen presenting cells (APC). N-Acetyl Cysteine (NAC) is a precursor of glutathione, while glutathione itself increases IL-12 production. Treatment with NAC combined with artemisinin is supposed to increase cellular immunity of mice during Plasmodium berghei infection. The aim of this study was to measure the effects of NAC administration on the degree of parasitemia and plasma IL-12 level in mice infected with P. berghei and treated with artemisinin. Methods The research was done using post-test-control-only design using 5 groups: group A (negative control group), group B (positive control group, or mice infected with P.berghei without therapy), group C ( mice infected by P.berghei and received artemisinin 0.04 mg/g BW for 7 days), group D (mice infected with P.berghei and received artemisinin in combination with NAC 1 mg/g BW for 7 days) and group E (mice infected wirth P.berghei and received artemisinin in combination with NAC 1 mg/g BW for 3 days and tapered into ½ mg/g BW for 4 days). Parasitemia was followed up every two days. Approximately six days post infection or when the degree of parasitemia reached ± 10% therapy was begun. On the 3rd, 5th, and 7th days post therapy, mice from each group were terminated and assayed for plasma IL-12 level (ELISA, Bender Medsystems GmbH, Vienna, cat. BMS6004). Results All mice treated with artemisinin mono-therapy and combined therapy had significantly decreased parasitemia (P=0.000). There was no significant difference (P>0.05) in decreasing parasitemia among treatment groups. The plasma IL-12 level increased significantly in both groups that received the combination of artemisinin and NAC constant dose and tapering dose compared with the group that received artemisinin mono-therapy (p < 0,05). Plasma IL-12p70 level in the combination of artemisinin and NAC tapering dose therapy group was higher than other groups on the 5th and 7th days post therapy. Conclusion The conclusion of this research is that artemisinin mono-therapy decreased parasitemia effectively as well as the combination therapy of artemisinin and NAC. Artemisinin and NAC therapy, constant and tapering dose, increase plasma IL-12p 70 level more than artemisinin mono-therapy does. The highest plasma IL-12p70 level was found in the artemisinin plus NAC tapering dose therapy group with seven days duration of therapy. (Med J Indones 2009; 18: 5-9) Keywords: N-acetyl Cysteine, Parasitemia, Interleukin-12, Plasmodium berghei